Onychomadesis associated with hand, foot, and mouth disease: a prospective observational study from North Chennai - Pichaachari, Saraswathy; Nagappan Subramaniam, Jayanthi; Sundaram, Sajeetha (International Journal of Research in Dermatology, 2020)
Background: Hand, foot, and mouth disease (HFMD) is a common febrile illness caused by coxsackievirus A16 and human enterovirus 71 characterized by vesicular eruptions on hands and feet and enanthem on oral mucosa. Resolves usually without complications but onychomadesis can occur as a late sequlae sometimes. Methods: Children with clinical diagnosis of HFMD between April to June 2018 were included in the study. Age, sex, duration of illness, cutaneous features and nail changes were noted at initial visit and during every week for next 6 weeks. Results: 58 children were recruited in the study with boys to girl’s ratio 1.2:1. The average age was 5.3 years. The vesicular lesions predominantly involved palms and soles (88.3%). 65.5% had history of fever and pruritis was the commonest cutaneous symptom. 27 children (48.21%) developed onychomadesis during follow up with average time interval of 3.2 weeks between the clinical diagnosis and nail shedding. Reassurance about spontaneous resolution of the condition given to the parents. Conclusions: Our study strengthened the association between the HFMD and occurrence of onychomadesis. Physician’s awareness about this benign condition is needed to avoid parental anxiety, unnecessary investigations and treatment for the children.